PRACTICAL USE OF EXTRACORPOREAL MEMBRANE OXYGENATION IN ORGAN DONATION FOR TRANSPLANTATION - M.G. Minina; M.Sh. Khubutia; K.K. Gubarev; V.A. Gulyaev; A.V. Pinchuk; M.M. Kaabak; B.V. Dabasambueva (Вестник трансплантологии и искусственных органов, 2012)
In Russia more than 50% of effective donors are non – heartbeating donors. As we all know, they appear mainly as the source of kidney transplants. The perfusion in situ through DBTL catheter is the most frequent technique usable. The rate of delayed graft function (DGF) following the DBTL perfusion may vary from 48 to 78,4%. ECMO technology use in organ donation may lead to dramatic decrease in DGF and create premises for multiorgan explantation. In the following paper we present the first Moscow experience of ECMO use in our practice of organ donation.